A Focus on Risk: States Reconsider Their Environmental Priorities - Minard, Richard (Maine Policy Review, 1991)
Richard Minard explains how the “comparative risk” process can be used as a tool to manage change. He explains how focusing on risk can help states build a more appropriate and resilient set of environmental priorities and create more effective strategies to address them. He illustrates his points with the results from state projects in Vermont, Louisiana and Washington and from national projects conducted by the U.S. Environmental Protection Agency (EPA)
Keywords: environmental risk; risk perception; environmental protection